PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAM ACCHIEVEMENT (STAD) PADA HASIL BELAJAR SEJARAH KELAS X DI SMA NEGERI 5 LUBUKLINGGAU - Ahmad Oviko; Agus Susilo Agus Susilo; Yeni Asmara Yeni Asmara (Universitas Labuhanbatu, 2022)
The purpose of the study was to determine the learning outcomes of the students of class X IPS 1 SMAN 5 Lubuklinggau History after the application of the STAD learning model media was significantly completed or not. The research method used was quasi-experimental, the research design was Pretest-Posttest Group design. Data collection techniques using the test technique. Data analysis technique with steps: normality test and t test. Based on data analysis, it is known that the results of the initial test (pre-test) with an average value of 61.88 pre-test and an average value of the final test (post-test) of 84.22. This shows that the average value of the final test (post-test) is greater than the initial test (pre-test) with a difference in value of 22.34. After being calculated using the Z-test, the value of zcount = 6.43 which is compared to the value of ztable with a significant level of 5% is 2.26. So the value of zcount > ztable or 6.43 > 2.26. So it can be concluded that the social studies learning outcomes of class X IPS 1 SMAN 5 Lubuklinggau students after the application of the STAD learning model media are significantly completed, the academic year 2021/2022.Keywords: Application, Cooperative Learning Model Type Student Team Achievement Division (STAD), Learning Outcomes.Abstrak Tujuan penelitian adalah untuk mengetahui hasil belajar Sejarah siswa kelas X IPS 1 SMAN 5 Lubuklinggau setelah penerapan media model pembelajaran STAD signifikan tuntas atau tidak. Metode penelitian yang digunakan eksperimen semu, desain penelitiannya Pretest-Posttest Group design. Teknik pengumpulan data menggunakan dengan teknik tes. Teknik analisis data dengan langkah-langkah: uji normalitas dan uji t. Berdasarkan analisis data, diketahui hasil tes awal (pre-test) dengan nilai rata-rata pre-test 61,88 dan nilai rata-rata tes akhir (post-test) sebesar 84,22. Hal ini menunjukkan bahwa nilai rata-rata tes akhir (post-test) lebih besar daripada tes awal (pre-test) dengan selisih nilai sebesar 22,34. Setelah dihitung dengan menggunakan uji-Z diperoleh nilai zhitung = 6,43 yang dibandingkan dengan nilai ztabel dengan taraf signifikan 5% adalah 2,26. Jadi nilaiÂ zhitung > ztabel atau 6,43 > 2,26. Maka dapat disimpulkan bahwa hasil belajar IPS siswa kelas X IPS 1 SMAN 5 Lubuklinggau setelah penerapan media model pembelajaran STAD signifikan tuntas, Tahun ajaran 2021/2022.Â Kata Kunci: Penerapan, Model, (STAD), Hasil Belajar